Transcervical (SP) and Transhiatal DaVinci Robotic Esophagectomy: A Cadaveric Study - van der Sluis, Pieter; Egberts, Jan-Hendrik; Stein, Hubert; Sallum, Rubens; van Hillegersberg, Richard; Grimminger, Peter P. (The Thoracic and Cardiovascular Surgeon, 2020)
Background This is a preclinical cadaveric study to investigate the feasibility of a fully robotic McKeown esophagectomy in simultaneous rendezvous technique using the DaVinci X for transhiatal dissection and the DaVinci single port (SP) for transcervical dissection.Methods Two transcervical esophagectomies with the DaVinci SP surgical system were performed as training procedures. In the third transcervical cadaveric procedure, the DaVinci SP was installed for the transcervical approach and the DaVinci X surgical system for the abdominal transhiatal phase. Primary outcomes were operating time and lymphadenectomy.Results The mobilization of the esophagus was successfully completed in 118 minutes by using the DaVinci SP for the transcervical phase and the DaVinci X for the transhiatal abdominal phase simultaneously. In total 18 lymph nodes were dissected in the thorax; 3 were located paratracheal right, 3 paratracheal left, 4 subcarinal, 4 para-aortic, 2 paraesophageal upper mediastinal, and 2 paraesophageal middle mediastinal.Conclusion This preclinical study demonstrated that a fully robotic McKeown esophagectomy in simultaneous rendezvous technique using the DaVinci X for transhiatal dissection and the DaVinci SP for transcervical dissection was feasible with adequate lymphadenectomy in a cadaver model. Future research will elucidate the indications for the use of the fully robotic transhiatal and transcervical esophagectomy.
Keywords: minimally invasive surgery; esophageal surgery; robotic